Solutions for sustainable mariculture - avoiding the adverse effects of mariculture on biological diversity - Armah, Ayi Kwei (2004)
The Ad Hoc Technical Expert Group on Mariculture was established by the Conference of the Parties in adopting the programme of work on marine and coastal biological diversity at its fourth meeting (decision IV/5, annex). The Expert Group was established to assist the Subsidiary Body on Scientific, Technical and Technological Advice (SBSTTA) in its work on the topic of mariculture. The terms of reference instructed the Expert Group to: (a) Evaluate the current state of scientific and technological knowledge on the effects of mariculture on marine and coastal biodiversity; (b) Provide guidance on criteria, methods, techniques and best practices that avoid the adverse effects of mariculture, and also subsequent stock enhancement, on marine and coastal biological diversity and enhance the positive effects of mariculture on marine and coastal productivity. In evaluating the current state of knowledge on the effects of mariculture on marine and coastal biodiversity, the group identified the main mariculture species and methods, and the biodiversity effects of those methods (Chapter 2). The group agreed that all forms of mariculture affect biodiversity at the genetic, species and ecosystem level, but that under certain circumstances mariculture could also enhance biodiversity locally (Chapter 4). The main effects include habitat degradation, disruption of trophic systems, depletion of natural seedstock, transmission of diseases, and reduction of genetic variability. The biodiversity-effects of pollutants- such as chemicals and drugs - are not very well studied, though are generally assumed to be negative. There are many available methods and techniques for avoiding the adverse effects of mariculture on biodiversity, and they are summarized in Chapter 3 of this document. They include, most importantly, proper site selection, as well as optimal management including proper feeding. Other mitigation measures include culturing different species together (polyculture), and the use of enclosed, and especially re-circulating, systems. Many of the other impacts can be avoided with better management practices and other technological improvements. A number of aquaculture-specific international and regional principles, standards and certification processes exist, and are described in Chapter 5 of this document.